Observations of the uptake of carbonyl sulfide (COS) by trees under elevated atmospheric carbon dioxide concentrations (Biogeosciences, 2012)
. Global change forces ecosystems to adapt to elevated atmospheric concentrations of carbon dioxide (CO2). We understand that carbonyl sulﬁde (COS), a trace gas which is involved in building up the stratospheric sulfate aerosol layer, is taken up by vegetation with the same triad of the enzymes which are metabolizing CO2, i.e. ribulose-1,5- bisphosphate carboxylase/oxygenase (Rubisco), phosphoenolpyruvate carboxylase (PEP-Co) and carbonic anhydrase (CA). Therefore, we discuss a physiological/biochemical acclimation of these enzymes affecting the sink strength of vegetation for COS. We investigated the acclimation of two European tree species, Fagus sylvatica and Quercus ilex, grown inside chambers under elevated CO2, and determined the exchange characteristics and the content of CA after a 1–2 yr period of acclimation from 350 ppm to 800 ppm CO2. We demonstrate that a compensation point, by deﬁnition, does not exist. Instead, we propose to discuss a point of uptake afﬁnity (PUA). The results indicate that such a PUA, the CA activity and the deposition velocities may change and may cause a decrease of the COS uptake by plant ecosystems, at least as long as the enzyme acclimation to CO2 is not surpassed by an increase of atmospheric COS. As a consequence, the atmospheric COS level may rise causing an increase of the radiative forcing in the troposphere. However, this increase is counterbalanced by the stronger input of this trace gas into the stratosphere causing a stronger energy re- ﬂection by the stratospheric sulfur aerosol into space (Bruhl ¨ et al., 2012). These data are very preliminary but may trigger a discussion on COS uptake acclimation to foster measurements with modern analytical instruments.